Windows administration at the command line : - Mueller, John (Wiley Publishing, 2006)
The last thing you want as a busy systems administrator is to click endlessly through the Windows GUI every time you need to perform a simple task. Want a better solution? Windows Administration at the Command Line reacquaints you with the often-overlooked utilities accessible through the command line in Windows 2003, XP, and 2000. Locate files, check system status, secure and monitor systems, and best of all, save time by using scripts to automate your time-consuming management tasks. This practical book reveals all the command line utilities and puts them right at your fingertips. The only resource on the market with the complete set of Windows command line utilities, this hands-on reference gives you solutions that yield superior results compared to GUI-based utilities, increasing your productivity in the field.